Effects of Ultrasonography-Guided Transversus Abdominis Plane Block on Postoperative Analgesia, Gastrointestinal Motility, and Mobilization in Patients Delivering Cesarean Delivery Under Spinal Anesthesia: A Retrospective Study - Ayça Sultan Şahin; Muhammed Emir Yıldız; Kadir Arslan; Hale Çetin Arslan (Düzce Tıp Fakültesi Dergisi, 2023)
Aim: The aim of this study was to investigate the effect of ultrasonography (USG)-guided transversus abdominis plane (TAP) block on postoperative analgesia, gastrointestinal motility, and mobilization time in patients who had a cesarean section under spinal anesthesia. Material and Methods: The follow-up forms of the total 81 patients who had elective cesarean delivery under spinal anesthesia between March 2022 and June 2022 were reviewed retrospectively. The patients were divided into two groups, 41 patients as the TAP block applied group (group T) and 40 patients as the control group (group C). Demographic data of patients, visual analog scale (VAS) values at postoperative 2nd-, 4th-, 6th-, 12th-, and 24th-hour, tramadol requirements, non-steroidal anti-inflammatory drug (NSAID) and tramadol consumption, postoperative nausea-vomiting (PONV) status, initial gas release times and mobilization times were analyzed. Results: The VAS scores of the patients in group T at the postoperative period 2nd-, 4th-, and 6th-hour were significantly lower than those of group C (p